Desenvolvimento de sistema em fluxo empregando ultrassom para remoção de enxofre de óleo diesel - Nunes, Matheus Augusto Gonçalves (2011)
In this work, the development of a continuous flow process for sulfur removal from diesel oil is proposed. The process is based on the application of ultrasonic energy for increasing the oxidation reaction rate of sulfur compounds in presence of oxidizing reagents. For the development of ultrasound-assisted oxidative desulfurization (UAOD) system, parameters such as reagents amount, residence time and solvent for extraction were evaluated. The developed UAOD continuous flow system was applied to three diesel oil containing different total sulfur content and distinct sulfur species. For comparison, a similar process, but using mechanical stirring instead of ultrasound energy was tested to evaluate the ultrasound effect to increasing chemical reactions rates and improve the mass transfer between heterogeneous mixtures. In addition, the milder conditions of temperature and pressure, associated to the capacity for removing refractory sulfur compounds to the hydrodesulfurization process without using hydrogen, it makes the continuous flow UAOD process as a promising alternative for fuel production with lower sulfur content.